Emotion, thought and therapy : a study of Hume and Spinoza and the relationship of philosophical theories of emotion to psychological theories of therapy /: a study of Hume and Spinoza and the relationship of philosophical theories of emotion to psychological theories of therapy. (2022) - Neu, Jerome
No abstract available